2018
DOI: 10.1007/s13197-018-3362-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the free and glycosidically bound aroma potential of two important tomato cultivars grown in Turkey

Abstract: Free and glycosidically bound volatiles from two major tomato cultivars (Lycopersicon esculantum L. cv. Alida and Merve) of Turkey were determined. Free volatile compounds were extracted using liquid-liquid microextraction, while bound volatiles were extracted using solid phase extraction. The compounds were analyzed using GC-FID and GC-MS. Alida showed presence of, 39 free and 32 bound aroma compounds again 38 free and 31 bound aroma compounds is Merve. The odor activity values of the volatile compounds sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A wide variety of aglycones have been discovered within fruits, such as monoterpenes, sesquiterpenes, C 13 -norisoprenoids, benzenoids, hydroxyl esters, aliphatic alcohols, and furans. 1 Generally, GBVs in fruits show higher concentrations than their free counterparts, as has been reported in grape, 6 tomato, 7,8 cherry, 9 strawberry, 10 and kiwifruit. 11,12 Moreover, the proportion of glycosylated volatiles is variable among species, cultivars, and fruit tissue.…”
Section: ■ Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…A wide variety of aglycones have been discovered within fruits, such as monoterpenes, sesquiterpenes, C 13 -norisoprenoids, benzenoids, hydroxyl esters, aliphatic alcohols, and furans. 1 Generally, GBVs in fruits show higher concentrations than their free counterparts, as has been reported in grape, 6 tomato, 7,8 cherry, 9 strawberry, 10 and kiwifruit. 11,12 Moreover, the proportion of glycosylated volatiles is variable among species, cultivars, and fruit tissue.…”
Section: ■ Introductionmentioning
confidence: 66%
“…A wide variety of aglycones have been discovered within fruits, such as monoterpenes, sesquiterpenes, C 13 -norisoprenoids, benzenoids, hydroxyl esters, aliphatic alcohols, and furans . Generally, GBVs in fruits show higher concentrations than their free counterparts, as has been reported in grape, tomato, , cherry, strawberry, and kiwifruit. , Moreover, the proportion of glycosylated volatiles is variable among species, cultivars, and fruit tissue. Previous studies have identified aglycones of GBVs from fruits with different cultivars and quantitated their amounts by a semi-quantitation method, in which the concentrations were expressed as internal standard equivalents. ,,, So far, only a few studies have investigated the aroma contribution of aglycones using gas chromatography-olfactometry (GC-O) analysis. , For example, Garcia et al evaluated the bound aroma profiles of kiwifruit and found that vanillin, β-damascenone, and 2-phenylethanol were the odor-active aglycones in the hydrolysates of Hayward and Hort16A cultivars . However, as important aspects of the molecular sensory approach, cAEDA and aroma omission tests have not been applied to glycosylated aglycones in fruits.…”
Section: Introductionmentioning
confidence: 97%